DEVELOPMENT OF NUCLEAR ENERGY AND SAFETY MEASURES IN MODERN NUCLEAR POWER PLANTS (Educa Journal of Studies, 2026)
The article provides information on the development of nuclear energy, chain reactions occurring in nuclear reactors, factors ensuring their continuous operation, the impact of ionizing radiation on the cells of living organisms, and the mechanisms of biological changes. Modern nuclear power plants (NPPs) play a central role in the transition to low-carbon energy systems; however, safety concerns remain a significant barrier to their widespread adoption. This paper examines risk assessment methodologies and the implementation of advanced safety measures in nuclear power plants. It is highlighted that various biological changes occur in the organism as a result of exposure to ionizing radiation.
Keywords: Nuclear reactor, chain reaction, nuclear fuel, ionizing radiation, biological impact, living cell, nuclear energy, risk assessment, safety measures, public trust, regulatory frameworks, passive safety systems, nuclear innovations.